Wheat Panache: A pangenome graph database representing presence–absence variation across sixteen bread wheat genomes. Issue 3 (29th May 2022) - Bayer, Philipp E.; Petereit, Jakob; Durant, Éloi; Monat, Cécile; Rouard, Mathieu; Hu, Haifei; Chapman, Brett; Li, Chengdao; Cheng, Shifeng; Batley, Jacqueline; Edwards, David
Abstract: Bread wheat ( Triticum aestivum L.) is one of humanity's most important staple crops, characterized by a large and complex genome with a high level of gene presence–absence variation (PAV) between cultivars, hampering genomic approaches for crop improvement. With the growing global population and the increasing impact of climate change on crop yield, there is an urgent need to apply genomic approaches to accelerate wheat breeding. With recent advances in DNA sequencing technology, a growing number of high‐quality reference genomes are becoming available, reflecting the genetic content of a diverse range of cultivars. However, information on the presence or absence of genomic regions has been hard to visualize and interrogate because of the size of these genomes and the lack of suitable bioinformatics tools. To address this limitation, we have produced a wheat pangenome graph maintained within an online database to facilitate interrogation and comparison of wheat cultivar genomes. The database allows users to visualize regions of the pangenome to assess PAV between bread wheat genomes. Core Ideas: Graph pangenomes represent more genomic variants than reference genomes. We present a wheat graph pangenome based on 16 public assemblies. We present Wheat Panache, an online visual representation of this graph. Wheat Panache lets users search the graph for presence–absence variants. We also distribute the graph preindexed for Giraffe utilization.